Combined intravenous ribavirin and recombinant human interferon α1b aerosol inhalation for adenovirus pneumonia with plastic bronchitis in children: a case report and review of literature - Lin, Liangkang; Tang, Maoting; Li, Deyuan; Fei, Haotian; Zhang, Haiyang (Frontiers in Pediatrics, 2024)
Background: Human adenovirus (HAdV) infections in children can lead to profound pulmonary injury and are frequently associated with severe complications, particularly in cases concomitant with plastic bronchitis. Managing this condition presents significant challenges and carries an exceptionally high fatality rate. Regrettably, there are currently no specific antiviral agents that have demonstrated efficacy in treating severe adenovirus pneumonia in children.We report a 10-month-old infant suffering from severe adenovirus pneumonia combined with plastic bronchitis (PB). He received intravenous ribavirin combined with recombinant human interferon α1b (INFα1b) aerosol inhalation and his condition eventually improved. No side effects occurred during the treatment, and the long-term prognosis was favorable.In this case, the combination therapy of intravenous ribavirin and INFα1b seems to have contributed to the resolution of illness and may be considered for similar cases until stronger evidence is generated .